2021
DOI: 10.3390/jcm10051114
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Phenotyping and Function Testing in Thrombocytopenia

Abstract: Patients who suffer from inherited or acquired thrombocytopenia can be also affected by platelet function defects, which potentially increase the risk of severe and life-threatening bleeding complications. A plethora of tests and assays for platelet phenotyping and function analysis are available, which are, in part, feasible in clinical practice due to adequate point-of-care qualities. However, most of them are time-consuming, require experienced and skilled personnel for platelet handling and processing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…(4) Platelet-platelet contact is not required as functional parameters are monitored on a single platelet. This enables platelet function analysis in thrombocytopenic samples, such as immune thrombocytopenia and combined platelet function and number disorders [ 52 ]. Our data clearly demonstrate that age-dependent changes of platelet reactivity and the achievement of adult platelet function depend on the agonist used and the platelet activation parameter.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Platelet-platelet contact is not required as functional parameters are monitored on a single platelet. This enables platelet function analysis in thrombocytopenic samples, such as immune thrombocytopenia and combined platelet function and number disorders [ 52 ]. Our data clearly demonstrate that age-dependent changes of platelet reactivity and the achievement of adult platelet function depend on the agonist used and the platelet activation parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma isolated by plasmapheresis is theoretically free from cellular elements, a small amount of platelets, leukocytes, and red blood cells were found in some of our samples. In control samples, approximately 10 × 10 9 /L platelets were measured compared to manually isolated PPP (platelet-poor plasma), which contains 34.5 × 10 9 /L [ 27 ]; however, the platelet count in plasma highly depends on the isolation method, and the normal platelet count of whole blood is 150–450 × 10 9 /L [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…We observe that a number of these papers are already viewed at a high rate and even cited, supporting the value of this article series. For this issue, we acquired one original research article [1] and 13 reviews [2][3][4][5][6][7][8][9][10][11][12][13][14] that are shortly introduced below.…”
mentioning
confidence: 99%
“…It is demonstrated that a low or high potential to generate procoagulant platelets in vitro may be associated with bleeding or thrombotic tendencies, respectively. A short summary of the thrombocytopathy associated with COVID-19 is added (for a discussion of platelet function testing, specifically in thrombocytopenic patients, see also the review by Jurk and Shiravand [11] introduced below).…”
mentioning
confidence: 99%
See 1 more Smart Citation